Welfare analysis in a Schumpeterian growth model with capital - Hagedorn, Marcus,Kaul, Ashok,Reinthaler, Volker (IZA, 2001)
In this note we compare the laissez-faire steady-state solution in the Howitt and Aghion (1998) model to the social optimum. The analysis offers several new insights in comparison to the welfare analysis in Aghion and Howitt (1992). We find various new distortions between private and optimal solution. First, a monopoly distortion effect generates too little capital accumulation in the private solution because households' gross return per unit of capital will be lower than in the social optimum due to monopoly power. Second, a cost-benefit gap effect leads to excessive research in the private solution because the planner is interested in the average technology whereas the private researcher is interested in the leading edge technology. Third, we decompose the well-known intertemporal spillover effect into three subeffects and clarify why the planner uses the interest rate as discount rate.
Keywords: Arbeitspapier; Graue Literatur; Soziale Wohlfahrtsfunktion; Pareto-Optimum; Neoklassisches Wachstumsmodell; Vergleich; Endogenes Wachstumsmodell; Investition; Innovation; Technischer Fortschritt; Theorie; social planning model